Esports assessment - Tholl, C.; Krampe, L.; Bickmann, P.; Soffner, M.; Froböse, I. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
This chapter deals with the physical and cognitive requirements of esports athletes, which are still insufficiently defined and quantified at this point. Due to this knowledge gap, esports assessments are necessary, which objectively measure different skill areas of esports athletes. The German Sport University Cologne has therefore developed one of the first comprehensive assessments in the field of esports, which allows the generation and classification of comparative values to traditional sports and can be used to create training concepts. As this is the first developed assessment battery in the field of esports based on valid measurement methods, it should continue to be elaborated in an evidence-based manner and adapted to the specific requirements of esports in the future.